Karya Tari “Berpijak Diatas Puing” Interpretasi Cerita Yang Terdapat Dalam Tari Tradisi Sikambang Di Kabupaten Pesisir Selatan - Fahrezi, Ingles; Loravianti, Susas Rita (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The dance work Berpijak Diatas Puing (Standing Amid the Ruins) is inspired by Tari Sikambang, a traditional Minangkabau dance originating from Nagari Kambang Utara. It tells the story of a Datuak (a traditional leader) who is devastated by the loss of his only child. This piece portrays inner conflict and emotional resilience in the face of tragedy, carrying the message that one must continue moving forward even in the midst of destruction. Developed with a dramatic approach and a social theme, the choreography incorporates traditional Sikambang movements such as Sipotong Geleang, Baraba Mandi, and Ratok, blended with contemporary techniques learned during the choreographer’s studies at the Indonesian Institute of the Arts Padangpanjang, including jumps, leaps, rolls, and more. Performed by nine dancers and one monologue character, the piece features live music and symbolic props, including black and white cloths representing grief and acceptance. This work serves as both an effort to preserve cultural heritage and a reflection on themes of loss, acceptance, and inner strength.